1997
DOI: 10.1046/j.1365-3040.1997.d01-17.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar repression of photosynthesis: the role of carbohydrates in signalling nitrogen deficiency through source:sink imbalance

Abstract: The aim of this work was to examine whether carhohydrates are involved in signalling N deficiency through sourcersink imbalance. Photosynthetic metaholism in tohacco was studied over 8 d during the withdrawal of N from previously N-sufficient plants in which the source:sink ratio was manipulated hy shading leaves on some of the plants. In N-sufficient plants over this timescale, there was a small decline in photosynthetic rate, Ruhisco protein and amino acid content, with a larger decrease in carhohydrate cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
198
3
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(220 citation statements)
references
References 36 publications
15
198
3
4
Order By: Relevance
“…7). Higher concentrations of soluble sugars such as Glc, Fru, and Suc, in the leaves of LN plants (Rufty et al, 1988;Paul and Driscoll, 1997) are known to enhance the expression of wound-induced PI genes as well as the expression of vegetable storage proteins in other species (Johnson and Ryan, 1990;Mason et al, 1992). A similar disconnect between metabolite and transcript accumulation was found in the accumulation of phenolic metabolites (chlorogenic acid and rutin) and their associated biosynthetic transcripts (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…7). Higher concentrations of soluble sugars such as Glc, Fru, and Suc, in the leaves of LN plants (Rufty et al, 1988;Paul and Driscoll, 1997) are known to enhance the expression of wound-induced PI genes as well as the expression of vegetable storage proteins in other species (Johnson and Ryan, 1990;Mason et al, 1992). A similar disconnect between metabolite and transcript accumulation was found in the accumulation of phenolic metabolites (chlorogenic acid and rutin) and their associated biosynthetic transcripts (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The accumulation of starch at low N is a well-established phenomenon (Rufty et al 1988;Paul and Stitt 1993;Paul and Driscoll 1997). Thus, the increasing nitrogen supply using nitrate, ammonium or ammonium nitrate, all resulted in lower starch concentrations in the present paper.…”
Section: Sex-specific Difference Of Biomass Accumulation and Allocationmentioning
confidence: 52%
“…Starch accumulation in leaves, by maintaining stromal P i cycling, allows A to continue unchanged (Stitt, 1991), and by lowering the amount of soluble sugar in the cytosol reduces the source of the regulatory signal that, according to Van Oosten & Besford (1996), might effect coarse control of the photosynthetic genes. Paul & Driscoll (1997), by manipulating the source-sink ratio of Nicotiana tabacum, found that the loss of photosynthetic activity was more correlated to the hexose : amino acid ratio than to sugar concentration per se, and concluded that the regulatory signal causing repression of A depends more crucially on the carbon : nitrogen ratio than on the carbohydrate status of leaves. Accordingly, the increased leaf carbon : nitrogen ratio, i.e.…”
Section: mentioning
confidence: 99%